Educational and Multidisciplinary innovation for sustainability in the Ocean i3 project - Usin Enales, Sandra; García Azpuru, Amaia; Elorriaga Illera, Angeriñe (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Universities are making important contributions to the fulfillment and achievement of the Sustainable Development Goals (SDGs). This communication describes the International Educational Innovation Project, Ocean i3, during its four editions (from 2018 to the present), promoted by the University of the Basque Country and the University of Bordeaux, in collaboration with Euskampus. A project in line with the Sustainable Development Goals 2030 (RBL-ODS), specifically the one related to the conservation and sustainability of the oceans, seas and marine resources, based on the development of transversal skills and methodologies based on Research Based Learning.